Strategic communications for nonprofit organizations seven steps to creating a successful plan - Patterson, Sally J. (Wiley, 2009)
"Completely rewritten and comprised of virtually all-new material, Strategic Communications for Nonprofit Organizations, Second Edition offers your nonprofit organization a conceptual framework and step-by-step process for developing an easy-to-implement strategic communications plan." "Based on the Core principles and approach developed by Radiant Communications, this much-needed volume explains how to transform theory into practice. It encourages nonprofits to be smart in their communications work, to use their limited resources successfully; and to evaluate the impact of their community outreach. Filled with proven techniques to ensure that nonprofits send the right message to each constituency group or audience, Strategic Communications for Nonprofit Organizations, Second Edition equips nonprofit professionals to coordinate their efforts to hit the mark every time."--Jacket
Keywords: Nonprofit organizations; Associations sans but lucratif / Marketing; Publicité-plaidoyer; Publicité institutionnelle; BUSINESS & ECONOMICS / Green Business; Advocacy advertising / Planning; Institutional advertising / Planning; Nonprofit organizations / Marketing / Planning; Niet-commerciële organisaties; Strategische planning; Communicatie; Kommunikation; Wirtschaft